Advances in hard X-ray RIXS toward meV resolution in the study of 5d transition metal materials - Kim, Jungho; Huang, Xiangrong; Toellner, Thomas; Said, Ayman (Frontiers in Electronic Materials, 2024)
Resonant inelastic X-ray scattering (RIXS) has played a pivotal role in advancing our understanding of spin-orbit physics in 5d transition metal materials. The progress in RIXS techniques has closely paralleled improvements in energy resolution, which have enabled the study of very low-lying excitations and led to the discovery of numerous new phenomena with significant scientific and technological implications. The multi-bend achromat (MBA) lattice upgrade of third-generation synchrotron sources, such as the Advanced Photon Source (APS), heralds a transformative era by introducing enhancements in brilliance and emittance. These advancements provide an opportunity to push the boundaries of RIXS techniques, meeting the challenges at the research frontiers of material science. This article aims to highlight key instrumental and technical advancements that enable the achievement of meV resolution in RIXS and discuss the impact of such high-resolution RIXS on exploring spin-orbit physics in 5d transition metal materials.